Documenting diagnosis in child and adolescent mental healthcare: A content analysis of diagnostic statements in a psychiatric case register. (June 2020) - O'Connor, Cliodhna; Downs, Johnny; McNicholas, Fiona; Cross, Lauren; Shetty, Hitesh
Highlights: Little research explores diagnostic practice in child and adolescent mental healthcare. This study analyses the contexts in which diagnostic terms appear in clinical notes. Nearly half of mentions of diagnostic terms involved confirmations of that diagnosis. A range of strategies were used to qualify and exclude diagnoses. Results highlight the complex and contingent nature of diagnostic decision making. Abstract: Understanding clinical practice in relation to psychiatric diagnosis is important for identifying avenues for service improvement, developing clinically valid research methods and informing debate about prevailing diagnostic systems. Minimal research has explored psychiatric diagnostic practice by studying the diagnostic information present in clinical records. This study identifies, quantifies and descriptively analyses the range of contexts in which diagnostic terms appear in free-text child and adolescent clinical notes. Text segments containing a diagnostic term ( N = 2993) were extracted from children's electronic health records and subjected to content analysis. Segments were coded as indicating: definite diagnostic confirmations (49.4%), qualified diagnostic confirmations (6.4%), diagnostic queries/assessment (16.9%), definite diagnostic exclusions (3.1%), qualified diagnostic exclusions (2.2%), diagnostic status of another person (13.5%), or clinically irrelevant text (8.6%). Qualitative content analysis explored the linguistic patterns characterising these contexts of use. Results are considered in terms of their implications for service delivery, sociological analyses of psychiatric diagnosis, and the opportunities and challenges posed by applications of natural language processing techniques to electronic health records.